Connective Tissue Growth Factor Is Expressed in Malignant Cells of Hodgkin Lymphoma but Not in Other Mature B-Cell Lymphomas. Issue 2 (August 2015) - Birgersdotter, Anna; Baumforth, Karl R. N.; Wei, Wenbin; Murray, Paul G.; Sjöberg, Jan; Björkholm, Magnus; Porwit, Anna; Ernberg, Ingemar
Abstract : Connective tissue growth factor (CTGF) has a major role in development of fibrosis and in the wound-healing process. Microarray analysis of 44 classical Hodgkin lymphoma (cHL) samples showed higher CTGF messenger RNA expression in the nodular sclerosis (NS) than in the mixed cellularity (MC) subtype. When analyzed by immunohistochemical analysis, Hodgkin–Reed-Sternberg (H-RS) cells and macrophages in 23 cHLs and "popcorn" cells in 2 nodular lymphocyte predominant Hodgkin lymphomas showed expression of CTGF protein correlating with the extent of fibrosis. In NS, CTGF was also expressed in fibroblasts and occasional lymphocytes. Malignant cells in 32 samples of various non-Hodgkin lymphomas were negative for CTGF. A staining pattern of stromal cells similar to that of NS cHL was seen in anaplastic large cell lymphoma. Macrophages stained positively in Burkitt lymphomas and in some mantle cell lymphomas. The high occurrence of fibrosis in cHL may be related to CTGF expression by malignant H-RS cells.